Enhancing cancer patient care via nursing apps: a systematic review - Retnaningsih, Dwi; Sukesi, Niken; Nugraha, Rozaq Isnaini; Deraya, Reanita Anggis; Ni’mah, Maulida Izzatin; Putri, Iva Anissya; Selviana, Sinta (Intelektual Pustaka Media Utama, 2025)
Digital health interventions have been shown to be effective in improving the quality of life for cancer patients through education, symptom management, and psychosocial support. This research aims to identify application content that can enhance the quality of life for cancer patients. The method used is a systematic review based on the population, intervention, comparison, outcome, study design (PICOS) criteria. From the search, 941 articles were found in the JSTOR database (n = 11), Science Direct (n = 54), ProQuest (n = 609), and Springer Link (n = 267), with a publication period from 2019 to 2024. The keywords used include: nursing applications, cancer, application content, quality of life, and randomized clinical trials (RCT). The inclusion criteria encompass RCT published in peer-reviewed journals, written in English, and utilizing digital applications as interventions to improve the quality of life for cancer patients. This research includes patients aged 16-80 from various countries, including China, Turkey, Ireland, Taiwan, and Australia. The results show that digital interventions such as digital storytelling, education through applications, nurse support programs, and virtual reality significantly improve patients' quality of life. The intervention content includes six main themes: medical education, symptom management, psychosocial support, multidisciplinary interventions, physical activity, and relaxation, as well as interactive digital platforms.